Artificial Intelligence Neuropathologist for Glioma Classification using Deep Learning - CHIHI, Oussama; LALMI, Ahmed Nidhal (My University, 2022)
"يعد تشخيص الصور الطبية من أكثر المشكلات تحديًا في مجال البحث لتحليل فحص التصوير بالرنين المغناطيسي. يعد الاكتشاف العصبي للأنواع الفرعية للورم الدبقي أمرًا أساسيًا لترتيب العلاج والتنبؤ به. يعتمد التحديد النسيجي القياسي للورم الدبقي على شرائح الهيماتوكسيلين المصبوغة بعد العملية الجراحية والأيوزين بواسطة أطباء الأمراض العصبية. مع التقدم في التفكير من صنع الإنسان (AI) ، كان الهدف من هذه المراجعة هو تحديد ما إذا كان يمكن تطبيق التعلم العميق على مجموعات الورم الدبقي. في مجال التصوير الطبي والتشخيص بمساعدة الكمبيوتر ، تتم مناقشة جميع النظريات والمفاهيم المرتبطة بمعالجة الصور والتعلم الآلي وطرق التحسين. تُستخدم أنظمة الكشف بمساعدة الكمبيوتر الآن بشكل شائع للكشف الدقيق والصريح عن تشوهات الدماغ. CAD هي تقنية متعددة التخصصات تجمع بين عناصر الذكاء الاصطناعي ورؤية الكمبيوتر مع معالجة الصور للصور الإشعاعية وعلم الأمراض لمساعدة الأطباء في تفسير الصور الطبية. ينصب تركيز هذا العمل أولاً على عملية تعتمد على دمج مجموعة من الأساليب: عملية التجزئة: تم تصميم النظام المقترح على بنية ResU-Net وهي عبارة عن CNNs بالكامل ، والتي حققت تنفيذًا من الدرجة الأولى لتجزئة الصور الطبية تلقائيًا. خطوة استخراج الميزات: تُستخدم لاستخراج الخصائص المحددة للصورة ، والتي يتم من خلالها إنشاء ناقل سمة مميز ويمكن تصنيف الصور. يلعب دور الداعم للمصنفات. عملية التصنيف: استخدمنا خوارزمية SVM لتصنيف جميع الميزات المستخرجة. ""AI-driven solutions for auto contouring brain tumors. Based on contrast-enhanced imaging, it computes multiregional segmentations and/or multi-class classification of glioma tumors. The most difficult issue in /the realm of MRI/ scan is medical image diagnosis or medical image prognosis. Medical image analysis is used in oncology to decide the characteristics of cancer, plan treatment, and monitor the disease's progression. Glioma is a type of malignant brain tumor that has serious effects on cognitive functions and lowered the quality of patients' lives. The neurotic identification of glioma subtypes is essential for planning and anticipating therapies. Neuropathologists use postoperative hematoxylin and eosin-stained slides to localize glioma in the standard histological manner. The purpose of this research field is to establish a deep learning model used for glioma segmentation and classification to detect different lesions. Computer-aided systems for detection are now commonly employed for the accurate and explicit detection of brain abnormalities. To assist the interpretation of radiological and pathological images, CAD utilizes a multidisciplinary approach combining together different techniques of artificial intelligence and computer vision based on image processing methods. There are currently few methods for addressing glioma multiple classes challenges since they are mostly based on single-task approaches without taking the correlation between them into account. Here, for simultaneous glioma classification-based segmentation, we propose a fully automated multimodal MRI-based multi-task learning framework. "
mémoire master informatique
Keywords: معالجة الصور ، التعلم العميق ، الشبكة العصبية التلافيفية ، ResUnet، SVM ، التشخيص بمساعدة الكمبيوتر ، ورم الدماغ.; Image processing, Deep Learning, Convolutional Neural Network,ResUnet,SVM, Computer Aide Diagnostic, Brain tumor.